The effect of training in different subjects on improving residents’ knowledge and their satisfaction with educational methods - a study in Iran - Moghaddam, Omid Moradi; Dargahi, Helen; Arabshahi, Kamran Soltani (BMC medical education, 2025)
A resident or assistant is a qualified physician who usually practices medicine in a hospital or clinic under the direct or indirect supervision of a physician who specializes in that area. In addition to being learners, they are also responsible for patient care. This study was conducted to investigate the effect of training in different subjects on the improvement of residents' knowledge and their satisfaction with each of the educational methods used in the Intensive Care Unit (ICU). This quasi-experimental intervention study was conducted in 2023 on 90 residents who had completed their training in the ICU. Every month, a group of three residents visited Rasoul -Akram Hospital for rotation. This one-month rotation was divided into 3 periods of 10 days in three different ICUs. Four educational methods were used over a period of 5 months. An initial test was given to each group at the beginning of the training course. Each month, in addition to the scientific and skills training given in the morning sessions and during the visits, four training sessions were given weekly, and at the end of the rotation each group was tested again. The data were analyzed using SPSS (version 25). The mean scores of the residents improved after the training course, which was statistically significant (P < 0.001). The highest and lowest levels of resident satisfaction with educational methods were associated with training during the visit (3.34) and in the morning (2.23). There was a significant difference between gender and mean residents score in pharmacokinetics and principles of ultrasound (P < 0.05). There was also a significant difference between age and average residents score in pharmacokinetics, principles of ultrasound and principles of sepsis diagnosis (P < 0.05). Residents were more satisfied with training during the visit. It is recommended that the educational sessions and training during the visit are in line with the educational goals and objectives. N/A. This study is not a clinical trial.